Investigation of Classroom Assessment Literacy of University Teachers of Punjab: Jahan Ara Shams,1 Muhammad Zafar Iqbal, Muhammad Zafar Iqbal (PJDOL, 2023)
The main objective of the study was to investigate the assessment literacy of university teachers. The study was quantitative in nature. A survey was conducted to investigate the assessment literacy of regular teaching faculty of universities. A total of 5755 in public and private sector general universities in Lahore, Pakistan constituted the population of the study. A sample of 500 university teachers was randomly selected.